Diaphragm and preparation method thereof, battery, energy storage device and electric equipment
By forming a point array glue point on the surface of the diaphragm base membrane, the glue point gradually decreases along the edge to the center of the center, which solves the problem of low bonding performance of the diaphragm, and achieves higher adhesion performance and electrolyte infiltration. The impact on the dynamics performance of secondary battery.
Patent Information
- Application Number
- CN202411445009.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-24
AI Technical Summary
The adhesive performance of existing diaphragms is relatively low, which affects the dynamic performance of secondary batteries.
Design a separator with glue dots distributed in a dotted pattern on the surface of the base film. The thickness of the glue dots gradually decreases from the edge to the center. A crater morphology of the glue dots is formed through a specific preparation method to improve the slippage of the glue dots. Migration and bonding properties.
It improves the adhesion performance between the diaphragm and the electrode pole, enhances the infiltration of the electrolyte, and reduces the impact on the dynamic performance of the secondary battery.
Smart Images

Figure CN119361967A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a diaphragm and a preparation method thereof, a battery, an energy storage device and an electrical equipment. Background Art
[0002] Secondary batteries (such as lithium-ion batteries) are usually composed of a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, wherein the separator is located between the positive electrode sheet and the negative electrode sheet to separate the positive and negative electrodes and prevent the two electrodes from contacting and short-circuiting.
[0003] In order to improve the adhesion performance of the diaphragm, a layer of adhesive coating needs to be provided on the diaphragm. However, the provision of the adhesive coating will affect the electrolyte wettability of the diaphragm, thereby affecting the dynamic performance of the secondary battery. Although the related technology can form a dot matrix adhesive coating on the surface of the diaphragm based on the dot matrix coating technology to improve the electrolyte wettability of the diaphragm, thereby reducing the impact of the diaphragm on the dynamic performance of the secondary battery, there is still the problem of low adhesion performance of the diaphragm. Summary of the invention
[0004] In order to solve the above technical problems, the present application discloses a diaphragm and a preparation method thereof, a battery, an energy storage device and an electrical equipment, which improve the bonding performance of the diaphragm while reducing the impact on the kinetic performance of the secondary battery.
[0005] In the first aspect, the present application provides a diaphragm, comprising: a base film, and a glue layer, wherein the glue layer is arranged on at least one side surface of the base film; the glue layer comprises a plurality of glue dots distributed in a lattice shape, and the thickness of the glue dots gradually decreases from the edge of the glue dots to the center of the glue dots.
[0006] In some embodiments of the present application, the thickness of the glue dot is H, 2 μm≤H≤15 μm.
[0007] In some embodiments of the present application, the glue spot has a crater morphology with a raised edge and a depressed middle.
[0008] In some embodiments of the present application, the diameter of the glue dots is 200 μm to 4000 μm.
[0009] In some embodiments of the present application, the weight of the adhesive layer is M, the area of the base film is S, and the weight of the base film is 0.5 g / m 2 ≤M / S≤2.0g / m 2 .
[0010] In some embodiments of the present application, the base film has a thickness of 5 μm to 20 μm.
[0011] In some embodiments of the present application, the bonding strength between the diaphragm and the electrode plate is 2N / m to 10N / m.
[0012] In some embodiments of the present application, the glue dots include polymer particles, and the material of the polymer particles is selected from at least one of polyvinylidene fluoride and polymethyl methacrylate.
[0013] In a second aspect, the present application provides a method for preparing the diaphragm as described in the first aspect, comprising the following steps:
[0014] Applying glue layer solution to at least one side of the surface of the base film to form an initial structure of glue dots distributed in a dot matrix, wherein the glue layer solution includes a first solvent;
[0015] Dispensing a second solvent onto the surface of the initial structure of the glue dots to form a second solvent droplet, wherein the second solvent is a solvent that is insoluble or slightly soluble in the first solvent;
[0016] The initial structure of the glue dots having the second solvent droplets on the surface is subjected to a heating treatment. While the second solvent droplets are evaporated by the heat, the initial structure of the glue dots is cured by the heat to form the glue dots.
[0017] In some embodiments of the present application, the temperature of the heating treatment is 60°C to 90°C, and the boiling point of the second solvent is not higher than 90°C.
[0018] In some embodiments of the present application, the thickness of the second solvent droplet is 1 μm to 13 μm, and the diameter is 200 μm to 1000 μm.
[0019] In some embodiments of the present application, the first solvent is selected from water, and the second solvent is selected from at least one of dichloromethane, dichloroethane and carbon tetrachloride;
[0020] Alternatively, the first solvent is selected from at least one of dimethylacetamide and N-methylpyrrolidone, and the second solvent is selected from at least one of cyclohexane and cyclopentane.
[0021] In a third aspect, the present application provides a battery, comprising the diaphragm described in the first aspect, or the diaphragm prepared by the preparation method described in the second aspect.
[0022] In a fourth aspect, the present application provides an energy storage device, comprising a housing and at least one battery as described in the third aspect, wherein the battery is accommodated in the housing.
[0023] In a fifth aspect, the present application provides an electrical device, comprising the energy storage device described in the fourth aspect, wherein the energy storage device supplies power to the electrical device.
[0024] Compared with the prior art, this application has at least the following beneficial effects:
[0025] The present application provides a diaphragm and a preparation method thereof, a battery, an energy storage device and an electrical equipment, wherein the diaphragm includes a base film and a glue layer, wherein the glue layer is arranged on at least one side surface of the base film; the glue layer includes a plurality of glue dots distributed in a lattice shape, and the thickness of the glue dots gradually decreases from the edge of the glue dots to the center of the glue dots, which is beneficial for the polymer particles in the glue dots to slide toward the center and the periphery after being squeezed (for example, in a hot pressing process), so that they are more easily embedded in the pores of the electrode pole piece, thereby achieving "physical riveting" with the electrode pole piece and improving the bonding performance between the diaphragm and the electrode pole piece; and the glue layer with such a lattice structure can provide an infiltration path and space for the electrolyte, improve the electrolyte wettability of the diaphragm, and thus reduce the influence of the diaphragm on the kinetic performance of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 It is a photo of glue spots on the surface of the diaphragm in the related art;
[0028] Figure 2 This is a schematic diagram of the structure of a diaphragm in one embodiment of the present application;
[0029] Figure 3 This is a schematic diagram of the structure of a glue point in one embodiment of the present application;
[0030] Figure 4 A schematic diagram of a process for forming glue dots in one embodiment of the present application;
[0031] Figure 5 A schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application;
[0032] Figure 6 A schematic diagram of the structure of an energy storage system according to an implementation scheme of the present application;
[0033] Figure 7 This is a photo of the glue dots prepared in Example 2 of the present application.
[0034] Explanation of the accompanying drawings: 1-energy storage device, 2-electric energy conversion device, 3-first user load, 4-second user load, 10-base film, 20-glue layer, 21-glue point, 211-middle recessed area, 400-energy storage system, 410-high voltage cable, 420-first electric energy conversion device, 430-second electric energy conversion device. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0036] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.
[0037] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.
[0038] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0039] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.
[0040] It should be noted that, in the content of the present application, lithium-ion batteries are used as an example of batteries to explain the present application, but the batteries of the present application are not limited to lithium-ion batteries.
[0041] like Figure 1 As shown, the glue spots formed by the related technology have a "steamed bun"-like morphology with a raised center. Such glue spots have a higher degree of agglomeration and a greater cohesive force. After hot pressing, the sliding range of the polymer particles in the glue spots is limited. Therefore, such glue spots are not easy to fully bond with the diaphragm, resulting in low bonding performance of the diaphragm.
[0042] In view of this, the present application provides a diaphragm, such as Figure 2 As shown, it includes a base film 10 and a glue layer 20, and the glue layer 20 is arranged on at least one side surface of the base film 10; the glue layer 20 includes a plurality of glue dots 21 distributed in a dot matrix. Figure 3 As shown, the thickness of the glue dot 21 gradually decreases from the edge of the glue dot to the center of the glue dot.
[0043] In one embodiment, the glue layer 20 is disposed on the side of the base film 10 facing the positive electrode sheet; in one embodiment, the glue layer 20 is disposed on the side of the base film 10 facing the negative electrode sheet; in one embodiment, the glue layer 20 is disposed on both sides of the base film 10, and the two sides of the base film 10 face the positive electrode sheet and the negative electrode sheet respectively.
[0044] The diaphragm provided by the present application has a glue point whose thickness gradually decreases from the edge of the glue point to the center of the glue point, and has a smaller cohesive force. After the glue point is compressed, the polymer particles in the glue point are more likely to slide toward the center and the periphery, that is, they have a larger sliding space, and thus are more easily embedded in the pores of the electrode pole piece, thereby achieving "physical riveting" with the electrode pole piece and improving the bonding performance between the diaphragm and the electrode pole piece; and, the glue layer of this lattice structure can provide an infiltration path and space for the electrolyte, improve the electrolyte wettability of the diaphragm, and thus reduce the influence of the diaphragm on the kinetic performance of the secondary battery.
[0045] In an optional embodiment, the thickness of the glue point is H, 2μm≤H≤15μm; in another optional embodiment, 4μm≤H≤10μm. For example, H is 2μm, 4μm, 5μm, 8μm, 10μm, 12μm or 15μm. It can be understood that the glue point of the present application has a structural feature of gradually decreasing from the edge to the center, and the thickest part of the glue point is usually located at the outer edge of the glue point. Based on this, the thickness of the glue point of the present application can refer to the thickness at the outer edge of the glue point. When the thickness of the glue point is too large (for example, greater than 15μm), it affects the ion transmission effect of the diaphragm, thereby affecting the dynamic performance of the lithium-ion battery; when the thickness of the glue point is too small (for example, less than 2μm), the polymer particles in the glue point have a small degree of slip after being compressed, and it is difficult to embed into the pores of the electrode plate, and the number of polymers that can be embedded in the middle of the electrode plate is small, and it is difficult to provide sufficient bonding strength, resulting in a decrease in the bonding performance between the diaphragm and the electrode plate. By adjusting the thickness of the glue point within the above range, it is beneficial to improve the bonding performance of the separator while reducing the impact on the kinetic performance of the secondary battery.
[0046] In an optional embodiment, reference Figure 3 The glue point 21 has a crater morphology with raised edges and a sunken middle. After being squeezed, the polymer particles in the glue point with this morphology are more likely to slide toward the center and the periphery, and are more likely to be embedded in the pores of the electrode plate, which is beneficial to improving the bonding performance between the diaphragm and the electrode plate.
[0047] In an optional embodiment, reference Figure 3 In the middle recessed area 211 of the glue dot 21, the base film 10 is exposed from the middle recessed area 211. In this way, the polymer particles in the glue dot have less resistance to sliding toward the middle recessed area after being squeezed, that is, it is easier to slide toward the middle recessed area, so it is easier to embed into the pores of the electrode plate, which is beneficial to improving the bonding performance between the diaphragm and the electrode plate. And because the base film 10 is exposed from the middle recessed area 211, the risk of pore blockage after the glue dot swells is reduced, thereby reducing the impact on the dynamic performance of the lithium-ion battery.
[0048] In an optional embodiment, the diameter of the glue dot is 200 μm to 4000 μm; in another optional embodiment, the diameter of the glue dot is 300 μm to 2000 μm. For example, the diameter of the glue dot is 200 μm, 500 μm, 800 μm, 1000 μm, 1500 μm, 2000 μm, 3000 μm or 4000 μm. The glue dot of the present application can be approximately regarded as a round dot, refer to Figure 3, the diameter of the glue dot refers to the size of the widest part of the glue dot in the horizontal direction, expressed as D. When the diameter of the glue dot is too small (for example, less than 200μm), in the process of forming the glue dot, the requirements for the precision of the glue dispensing equipment are higher, the morphology consistency of the glue dots distributed in a dot matrix is more difficult to control, and it is not conducive to improving the efficiency of glue dispensing; when the diameter of the glue dot is too large (for example, greater than 4000μm), under the condition of the same amount of glue layer coating, the number of glue dots distributed per unit area is too small, resulting in a small effective bonding area of the glue dot, which in turn leads to poor bonding performance between the diaphragm and the electrode plate. By adjusting the diameter of the glue dot within the above range, the bonding performance of the glue dot is guaranteed while maintaining the consistency of the morphology of the glue dot, and it is also conducive to improving the efficiency of glue dispensing.
[0049] In an optional embodiment, the weight of the adhesive layer is M, the area of the base film is S, and the thickness of the adhesive layer is 0.5 g / m 2 ≤M / S≤2.0g / m 2 For example, M / S is 0.5g / m 2 1.0g / m 2 , 1.5g / m 2 or 2.0g / m 2 By adjusting M / S within the above range, effective bonding between the diaphragm and the electrode plate can be achieved while avoiding an increase in the ionic resistance of the diaphragm due to excessive weight of the adhesive layer. The above M / S is defined as the single-sided surface density of the adhesive layer.
[0050] In an optional embodiment, the thickness of the base film is 5 μm to 20 μm. For example, the thickness of the base film is 5 μm, 10 μm, 15 μm or 20 μm. The present application has no particular limitation on the thickness of the base film, as long as a diaphragm with a glue layer can be obtained.
[0051] In an optional embodiment, the bonding strength between the diaphragm and the electrode plate is 2N / m to 10N / m. For example, the bonding strength between the diaphragm and the electrode plate is 2N / m, 4N / m, 5N / m, 8N / m or 10N / m. The above bonding strength includes the bonding strength between the diaphragm and the positive electrode plate or the bonding strength between the diaphragm and the negative electrode plate. By regulating the bonding strength between the diaphragm and the electrode plate within the above range, the diaphragm is less likely to peel off during the cycle of the lithium-ion battery, thereby improving the structural stability of the lithium-ion battery, and can also reduce the risks of powdering of the active material layer of the electrode plate and difficulty in electrolyte infiltration due to excessive bonding strength.
[0052] In an optional embodiment, the glue dots include polymer particles, and the material of the polymer particles is selected from at least one of polyvinylidene fluoride (PVDF) and polymethyl methacrylate (PMMA). The polymer particles can be particles that are approximately spherical, and the present application has no particular restrictions on the particle size of the polymer particles. For example, when the polymer particles are PVDF particles, the average particle size of the PVDF primary particles is 0.1 μm to 2 μm, the average particle size of the PVDF secondary particles is 5 μm to 8 μm, and the weight average molecular weight is 50 to 150; when the polymer particles are PMMA particles, the average particle size of the PMMA particles is 0.5 μm to 10 μm.
[0053] The present application also provides a method for preparing the diaphragm according to any of the above embodiments, comprising the following steps:
[0054] Step A, applying glue layer solution to at least one side of the surface of the base film to form an initial structure of glue dots distributed in a dot matrix, wherein the glue layer solution includes a first solvent;
[0055] Step B, dispensing a second solvent onto the surface of the initial structure of the glue point to form a second solvent droplet, wherein the second solvent is a solvent that is insoluble or slightly soluble in the first solvent;
[0056] Step C: heating the initial structure of the glue dots with the second solvent droplets on the surface, so that the second solvent droplets evaporate and the initial structure of the glue dots is cured by heat to form glue dots.
[0057] Figure 4 This is a schematic diagram of the process of forming glue dots in one embodiment of the present application, refer to Figure 4 In step A, the glue layer solution can be dispensed onto at least one side of the base film through the dot matrix coating head of the first dispensing device. It can be understood that the glue dots formed at this time are still in liquid state and do not have a morphology of thin center and thick edge, so it is called the initial structure of the glue dots. The first dispensing device can be a metering tube dispensing device, and its dot matrix coating head is needle-shaped with adjustable aperture, which has the advantage of high coating consistency.
[0058] The present application has no particular restrictions on the components of the adhesive layer solution, which may include a polymer, a dispersant, a binder and a first solvent. Among them, the dispersant includes but is not limited to at least one of polyacrylic acid (PAA), sodium polyacrylate, polyacrylate copolymer, carboxymethyl cellulose (CMC) and sodium carboxymethyl cellulose; the binder includes but is not limited to at least one of styrene-butadiene latex, styrene-acrylic latex, pure benzene latex, polymethyl methacrylate, polybutyl methacrylate, polyethyl acrylate, polyvinyl alcohol, ethylene-vinyl acetate copolymer, polyvinyl acetate and polyurethane; in addition, the adhesive layer solution may also include an auxiliary agent, which includes but is not limited to at least one of fluoroalkyl methoxy ether alcohol, fluoroalkyl ethoxy ether alcohol, polyoxyethylene alkylamide and fatty alcohol polyoxyethylene ether. In the adhesive layer solution, the mass fraction of the polymer is 85-90 parts, the dispersant is 1-5 parts, the binder is 5-10 parts, the auxiliary agent is 0-1 part, and the sum of the mass fractions of the above components is 100 parts.
[0059] In step B, the second solvent can be dispensed to the surface of the initial structure of the glue dots by the dot coating head of the second dispensing device to form second solvent droplets. The second solvent is a solvent that is insoluble or slightly soluble in the first solvent. Since the two are immiscible, the second solvent droplets can be supported on the surface of the initial structure of the glue dots. The initial structure of the glue dots is subjected to the downward pressure of the second solvent droplets and thus presents a morphology with a concave middle and raised surroundings. The second dispensing device can be a jet dispensing device, and its dot coating head is needle-shaped with an adjustable aperture.
[0060] In an optional embodiment, the temperature of the heating treatment is 60°C to 90°C, and the boiling point of the second solvent is not higher than 90°C. If the temperature of the heating treatment is too low, the second solvent is difficult to volatilize and the initial structure of the glue point is difficult to solidify; if the temperature of the heating treatment is too high, it will cause damage to the glue point and the base film. Based on this, the present application regulates the temperature of the heating treatment within the above range and selects a second solvent with the above boiling point range. On the one hand, it is beneficial for the second solvent to volatilize and the initial structure of the glue point to solidify during the heating process. On the other hand, it avoids damage to the glue point and the base film due to excessively high temperature, thereby improving the bonding performance of the diaphragm.
[0061] In an optional embodiment, the thickness of the second solvent droplet is 1μm to 13μm, preferably 3μm to 8μm, and the diameter is 200μm to 1000μm. For example, the thickness of the second solvent droplet is 1μm, 5μm, 10μm or 13μm, and the diameter is 200μm, 500μm, 800μm or 1000μm. When the thickness and diameter of the second solvent droplet are too small, the middle of the glue point is not easy to expose the base film, which is not conducive to improving the bonding performance between the diaphragm and the electrode plate; when the thickness and diameter of the second solvent droplet are too large, the effective bonding area of the glue point is small, which also leads to poor bonding performance. By regulating the thickness and diameter of the second solvent droplet within the above range, it is beneficial to improve the bonding performance between the diaphragm and the electrode plate.
[0062] In an optional embodiment, the first solvent is selected from water, the second solvent is selected from at least one of dichloromethane, dichloroethane and carbon tetrachloride, and the subbing layer solution is an aqueous system;
[0063] Alternatively, the first solvent is selected from at least one of dimethylacetamide (DMAC) and N-methylpyrrolidone (NMP), the second solvent is selected from at least one of cyclohexane and cyclopentane, and the glue layer solution is an oily system.
[0064] The present application does not particularly limit the method for regulating the thickness and / or diameter of the glue dots, as long as the purpose of the present application can be achieved. For example, the thickness and / or diameter of the glue dots usually increase with the increase of the aperture of the coating head of the dispensing equipment. Based on this, in the preparation process of the initial structure of the glue dots, the thickness and / or diameter can be regulated by regulating the aperture of the coating head of the metering tube dispensing equipment; or, the thickness and / or diameter of the glue dots can be regulated by regulating the characteristics of the glue layer solution itself, such as regulating the solid content, viscosity and other parameters of the glue layer solution. Generally, the smaller the solid content and viscosity of the glue layer solution, the smaller the glue dot thickness and glue dot diameter. Based on this, the most suitable formula and coating head can be selected in combination with the equipment capabilities and material characteristics.
[0065] The present application has no particular restrictions on the method for regulating the thickness and / or diameter of the second solvent droplet, as long as the purpose of the present application can be achieved. For example, the thickness and / or diameter of the second solvent droplet generally increases with the increase of the aperture of the coating head of the dispensing device. Based on this, the thickness and / or diameter of the second solvent droplet can be regulated by regulating the aperture of the coating head of the jet dispensing device during the formation of the second solvent droplet.
[0066] The present application provides a method for preparing a diaphragm, which prepares an initial structure of glue dots through a dispensing process, and innovatively utilizes the immiscible characteristics of the first solvent and the second solvent in the initial structure of the glue dots, dispensing the second solvent onto the surface of the initial structure of the glue dots to form a second solvent droplet, so that the initial structure of the glue dots presents a morphology of a concave middle and raised surroundings, and then forms glue dots with the morphological characteristics of the present application after heating treatment, which has the advantages of a simple preparation process and easy and precise control of process parameters. In addition, the prepared dot matrix glue dots can reduce the influence of the diaphragm on the dynamic performance of lithium-ion batteries while improving the bonding performance between the diaphragm and the electrode plate.
[0067] The present application also provides a battery, comprising the separator described in any of the above embodiments.
[0068] The lithium-ion battery of the present application also includes a positive electrode sheet. The present application has no special restrictions on the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet usually includes a positive current collector and a positive electrode material layer. The positive electrode material layer can be arranged on one surface in the thickness direction of the positive current collector, or on two surfaces in the thickness direction of the positive current collector. In the present application, the positive electrode material layer is arranged on the surface of the positive current collector, that is, the positive electrode material layer can be arranged in a partial area of one surface of the positive current collector, or in the entire area of one surface of the positive current collector. In the present application, there is no special restriction on the positive current collector, as long as the purpose of the present application can be achieved, for example, it can include but is not limited to aluminum foil, aluminum alloy foil or composite current collector. In the present application, there is no special restriction on the thickness of the positive current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the positive electrode material layer of the present application can be 8μm to 15μm.
[0069] In the present application, the positive electrode active material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, it may include at least one of lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide, lithium manganese oxide and lithium iron manganese phosphate.
[0070] In the present application, the positive electrode active material layer may also include a positive electrode binder. The present application has no particular limitation on the positive electrode binder as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of fluorine-containing resins, polypropylene resins, fiber-type binders, rubber-type binders or polyimide-type binders.
[0071] The lithium-ion battery of the present application also includes a negative electrode sheet. The present application has no special restrictions on the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the negative electrode sheet generally includes a negative electrode collector and a negative electrode material layer. The negative electrode material layer can be arranged on one surface or two surfaces along the thickness direction of the negative electrode collector. In the present application, the negative electrode material layer is arranged on the surface of the negative electrode collector, that is, the negative electrode material layer can be arranged in a partial area of one surface of the negative electrode collector, or in the entire area of one surface of the negative electrode collector. The present application has no special restrictions on the negative electrode collector, as long as the purpose of the present application can be achieved. For example, it can include but is not limited to copper foil, copper alloy foil, nickel foil or composite current collector. In the present application, there is no special restriction on the thickness of the negative electrode collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the negative electrode material layer of the present application can be 70μm to 200μm.
[0072] In the present application, the negative electrode material layer includes a negative electrode material, wherein the negative electrode material is not particularly limited as long as the purpose of the present application can be achieved. For example, it can include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon, hard carbon, silicon, and silicon carbon.
[0073] In the present application, the negative electrode material layer may further include a negative electrode binder. The present application has no particular restrictions on the negative electrode binder, as long as it can achieve the purpose of the present application, for example, it may include but is not limited to at least one of acrylate, polyamide, polyimide, polyamideimide, polyvinylidene fluoride, styrene-butadiene rubber, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, and potassium carboxymethyl cellulose.
[0074] The present application does not particularly limit the basement membrane of the diaphragm, and those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved. For example, the basement membrane is a non-woven fabric, a film or a composite film with a porous structure, and the material of the basement membrane is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film can be selected.
[0075] The battery of the present application also includes an electrolyte. The present application has no particular restrictions on the electrolyte, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, after mixing at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl propionate (EP), propyl propionate (PP), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC) or fluoroethylene carbonate (FEC) in a certain mass ratio or volume ratio to obtain a non-aqueous organic solvent, add a lithium salt to dissolve and mix evenly. The present application has no restrictions on the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include LiPF 6 , LiBF 4 、LiAsF 6 、LiClO 4 、LiB(C 6 H 5 ) 4 、LiCH 3 SO 3 、LiCF 3 SO 3 、LiN(SO 2 CF 3 ) 2 、LiC(SO 2 CF 3 ) 3 、LiSiF 6 At least one of lithium bis(oxalato)borate (LiBOB) or lithium difluoroborate. The present application has no particular limitation on the concentration of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, the concentration of the lithium salt is 1.0 mol / L to 2.0 mol / L.
[0076] The battery of the present application also includes a shell, and the present application has no particular limitation on the shell, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the shell may include an aluminum-plastic film.
[0077] The present application does not particularly limit the preparation method of the battery, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the battery includes but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain a bare cell with a wound structure, placing the bare cell in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a battery.
[0078] The present application also provides an energy storage device, including a housing and at least one battery in any of the above embodiments, wherein the battery is contained in the housing. The energy storage device having the battery has excellent performance, which is beneficial to the use of the energy storage device. By containing the battery in the housing, the fixation and protection of the battery can be increased, thereby improving the service life of the energy storage device. It is understandable that the energy storage device may have one or more batteries, and when the energy storage device contains multiple batteries, the multiple batteries may be connected in at least one of parallel and series connection.
[0079] The present application also provides an electrical device, including the energy storage device in the above-mentioned implementation scheme, which is conducive to improving the product competitiveness and performance of the electrical device. In an optional implementation scheme, the electrical device includes an electrical device body, and the energy storage device is used to supply power to the electrical device body. In an optional implementation scheme, the electrical device body includes a positive electrode of the device and a negative electrode of the device, the positive electrode plate of the battery in the energy storage device is used to electrically connect to the positive electrode of the device body of the electrical device, and the negative electrode plate of the battery in the energy storage device is used to electrically connect to the negative electrode of the device body of the electrical device, so as to supply power to the electrical device.
[0080] The electrical equipment of the present application may include but is not limited to: containers, household energy storage systems, battery vehicles, electric vehicles, ships, spacecraft, electric toys and electric tools, etc., wherein spacecrafts include airplanes, rockets, space shuttles and spacecrafts, etc., electric toys include fixed or mobile electric toys, such as electric car toys, electric ship toys and electric airplane toys, etc., and electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.
[0081] See also Figure 5 , Figure 5 This is a schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application, and the present application Figure 5 The implementation plan is described using a household energy storage scenario in user-side energy storage as an example, but the energy storage device of the present application is not limited to the household energy storage scenario.
[0082] The present application provides a household energy storage system, which includes an energy conversion device 2 (photovoltaic panel), a first user load 3 (street lamp), a second user load 4 (such as air conditioner and other household appliances), and an energy storage device 1. The energy storage device 1 is a small energy storage box that can be mounted on an outdoor wall by wall hanging. Specifically, the photovoltaic panel can convert solar energy into electrical energy during the period of low electricity prices. The energy storage device 1 is used to store the electrical energy and supply it to street lamps and household appliances for use during the peak electricity prices, or to supply power when the power grid is out of power / power outage.
[0083] See also Figure 6 , Figure 6 This is a schematic diagram of the structure of an energy storage system 400 according to an implementation scheme of the present application, and the present application Figure 6 The implementation plan is described using the shared energy storage scenario on the generation / distribution side as an example, and the energy storage device 1 of the present application is not limited to the energy storage scenario on the generation / distribution side.
[0084] The present application provides an energy storage system 400, which includes: a high-voltage cable 410, a first electric energy conversion device 420, a second electric energy conversion device 430 and an energy storage device 1 provided in the present application. In the case of power generation, the first electric energy conversion device 420 and the second electric energy conversion device 430 are used to convert other forms of energy into electric energy, which are connected to the high-voltage cable 410 and supplied to the power distribution network for use. When the power load is low and the first electric energy conversion device 420 and the second electric energy conversion device 430 generate excess power, the excess power is stored in the energy storage device 1, thereby reducing the wind and solar power abandonment rates and improving the problem of new energy power generation and consumption. When the power load is high, the power grid issues an instruction to transmit the power stored in the energy storage device 1 in conjunction with the high-voltage cable 410 in a grid-connected mode to the power consumption side, thereby providing peak shaving, frequency regulation, standby and other services for the power grid operation, giving full play to the peak shaving role of the power grid, promoting peak shaving and valley filling of the power grid, and alleviating the power supply pressure of the power grid.
[0085] Optionally, the first electric energy conversion device 420 and the second electric energy conversion device 430 can convert at least one of solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.
[0086] The number of energy storage devices 1 can be multiple, and multiple energy storage devices 1 are connected in series or in parallel. Multiple energy storage devices 1 are supported and electrically connected by isolation plates (not shown). In this embodiment, "multiple" refers to two or more. An energy storage box can also be provided outside the energy storage device 1 to accommodate the energy storage device 1.
[0087] Optionally, the energy storage device 1 may include but is not limited to a battery module, a battery pack, a battery system, etc. Among them, the battery module may be a battery module formed by connecting multiple batteries of the present application in series / parallel, the battery pack may include multiple batteries of the present application, and the battery system may be a charging and discharging system including the battery or battery pack of the present application.
[0088] The actual application form of the energy storage device 1 provided in the embodiment of the present application may be, but is not limited to, the listed products, and may also be other application forms. The embodiment of the present application does not strictly limit the application form of the energy storage device 1. The embodiment of the present application only takes the energy storage device 1 as a multi-core battery as an example for explanation. When the energy storage device 1 is a single battery, the energy storage device 1 may be at least one of a cylindrical battery, a square battery, and the like.
[0089] The diaphragm and the preparation method thereof of the present application are further described below in conjunction with more specific embodiments.
[0090] Example
[0091] Hereinafter, the embodiments of the present application will be described in more detail with reference to preparation examples, examples and comparative examples. Various tests and evaluations were performed according to the following methods.
[0092] Example 1
[0093] <Preparation of Separator>
[0094] <Preparation of Subbing Solution>
[0095] The polymer particles PVDF (average particle size 6 μm, weight average molecular weight 50-150), dispersant PAA, and binder CMC are mixed in a mass ratio of 90:2:8, and then the first solvent deionized water is added to prepare a glue layer solution. The mass percentage of the first solvent in the glue layer solution is 85%, and the mass percentage of dry matter is 15%.
[0096] <Preparation of Initial Structure of Glue Dots>
[0097] The prepared glue layer solution was dispensed onto one side of the base film using a time pressure type dispensing device (Musashi, Japan, model ML-5000XⅡ) to form an initial structure of glue dots distributed in a dot matrix.
[0098] <Preparation of glue dots>
[0099] A jet dispensing device (Vermes, Germany, model MDV3200A) was used to dispense the second solvent dichloromethane onto the surface of the initial structure of the glue dots to form a second solvent droplet. The thickness and diameter of the second solvent droplet are shown in Table 1. The initial structure of the glue dots with the second solvent droplet on the surface was heated at 60°C for 5 minutes to form glue dots. The thickness and diameter of the glue dots are shown in Table 1.
[0100] <Preparation of positive electrode sheet>
[0101] The positive electrode active material lithium iron phosphate (LiFePO 4 ), conductive carbon black (Super-P), and binder PVDF are mixed in a mass ratio of 94:3:3; then N-methylpyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry with a solid content of 60wt%, and stirred evenly, and then the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and then after drying, cold pressing, slitting, cutting, welding the pole ears and other processes, a positive electrode sheet is obtained. The single-sided thickness of the positive electrode active material layer is 100μm.
[0102] Embodiment 2 to Embodiment 6
[0103] Except that the thickness of the second solvent droplet, the diameter of the second solvent droplet, the thickness of the glue dot, and the diameter of the glue dot are adjusted according to Table 1 in <Preparation of the diaphragm>, the rest is the same as Example 1.
[0104] Embodiment 7 to Embodiment 9
[0105] Except that the thickness of the base film was adjusted according to Table 1 in <Preparation of Separator>, the rest was the same as Example 3.
[0106] Example 10 to Example 12
[0107] Except that the single-sided surface density of the adhesive layer was adjusted according to Table 1 in <Preparation of Separator>, the rest was the same as Example 3.
[0108] Example 13 to Example 16
[0109] Except that the relevant preparation parameters in <Preparation of diaphragm> are adjusted according to Table 2, the rest is the same as Example 2.
[0110] Comparative Example 1 to Comparative Example 2
[0111] Except that the thickness of the second solvent droplet, the diameter of the second solvent droplet, the thickness of the glue dot, and the diameter of the glue dot are adjusted according to Table 1 in <Preparation of the diaphragm>, the rest is the same as Example 1.
[0112] Comparative Example 3
[0113] The same as in Example 1 except that in <Preparation of Separator>, no second solvent droplet is formed on the surface of the glue dot initial structure, that is, the formed glue dot initial structure is directly heated to form glue dots.
[0114] Table 1 Preparation parameters of Examples 1 to 12 and Comparative Examples 1 to 3
[0115]
[0116] In Table 1, “ / ” indicates that there is no relevant preparation parameter.
[0117] Table 2 Preparation parameters of Example 2, Example 13 to Example 16
[0118] Polymer particle type First solvent type Second solvent type Example 2 PVDF water Dichloromethane Embodiment 13 PMMA water Dichloromethane Embodiment 14 PVDF water Carbon tetrachloride Embodiment 15 PVDF DMAC Cyclohexane Example 16 PVDF NMP Cyclopentane
[0119] Test methods and equipment
[0120] Glue point thickness test:
[0121] Use an online thickness gauge to measure the thickness of the glue dots.
[0122] Diaphragm bonding performance test:
[0123] The diaphragm and the electrode sheet (e.g., the positive electrode sheet) are stacked in the order of "positive electrode sheet-diaphragm-positive electrode sheet" as the test piece, and the hot pressing parameters are set: hot pressing temperature 25°C, hot pressing pressure 20 tons (T), hot pressing time 40s, and hot pressing is performed. After hot pressing, the positive electrode sheet corresponding to the side of the diaphragm without the glue layer is peeled off, and the hot pressed test piece is cut into 100mm*20mm strips. The bonding strength of the side of the diaphragm with the glue layer to the positive electrode sheet is tested using a tensile machine. The unit is N / m, where the test speed is 350mm / min and the test distance is 500mm.
[0124] Diaphragm ionic impedance test:
[0125] Referring to the ionic conductivity test method in 6.6.2 of the standard "GB / T 36363-2018 Polyolefin Separator for Lithium-ion Batteries", the ionic impedance of the separator was obtained by fitting with the number of separator layers as the horizontal axis and the resistance as the vertical axis.
[0126] Table 3 Performance data of Examples 1 to 16 and Comparative Examples 1 to 3
[0127]
[0128]
[0129] In combination with Table 1 and Table 3, it can be seen from Examples 1 to 6 and Comparative Examples 1 to 3 that when the thickness and diameter of the glue dots are too small (such as Comparative Example 1), the bonding strength of the diaphragm is low; when the thickness and diameter of the glue dots are too large (such as Comparative Example 2), the bonding strength of the diaphragm is also low; when the glue dots are not formed using the second solvent droplets (such as Comparative Example 3), the bonding strength of the diaphragm is low and the ionic impedance is high. This may be because the glue dots in Comparative Example 3 do not have the characteristics of thick edges and thin centers, and the glue dots have a higher degree of agglomeration and greater cohesion, which is not conducive to improving the bonding strength and reducing the ionic impedance.
[0130] Parameters such as the thickness of the base film and the single-sided surface density of the adhesive layer will also affect the performance of the diaphragm. It can be seen from Examples 7 to 12 that, based on the diaphragm structure of the present application, by adjusting the above parameters within the scope of the present application, it is beneficial to obtain a diaphragm with high bonding properties and low ionic impedance characteristics.
[0131] The type of polymer particles, the type of the first solvent and the type of the second solvent will usually also affect the performance of the diaphragm. It can be seen from Example 2 and Example 13 to Example 16 that, based on the diaphragm structure of the present application, by regulating the above parameters within the scope of the present application, it is beneficial to obtain a diaphragm with high bonding properties and low ionic impedance characteristics.
[0132] Figure 7 This is a photo of the glue dots prepared in Example 3 of the present application. It can be seen from the figure that the glue dots have a crater morphology with a raised edge and a depressed middle, and the diameter is about 800 μm.
[0133] The above is a detailed introduction to a diaphragm and its preparation method, a battery, an energy storage device and an electrical equipment and its preparation method disclosed in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core inventions of the embodiments of the present application; at the same time, for general technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A diaphragm, characterized in that: include: Basement membrane; and an adhesive layer, the adhesive layer being disposed on at least one side surface of the base film; The glue layer includes a plurality of glue dots distributed in a dot matrix, and the thickness of the glue dots gradually decreases from the edge of the glue dots to the center of the glue dots.
2. The diaphragm according to claim 1, characterized in that The thickness of the glue point is H, 2μm≤H≤15μm.
3. The diaphragm according to claim 1 or 2, characterized in that: The glue spot has a crater morphology with raised edges and a depressed middle portion.
4. The diaphragm according to claim 1 or 2, characterized in that: The diameter of the glue dots is 200 μm to 4000 μm.
5. The diaphragm according to claim 1 or 2, characterized in that: The weight of the adhesive layer is M, the area of the base film is S, 0.5 g / m 2 ≤M / S≤2.0g / m 2 .
6. The diaphragm according to claim 1 or 2, characterized in that: The base film has a thickness of 5 μm to 20 μm.
7. The diaphragm according to claim 1 or 2, characterized in that: The bonding strength between the diaphragm and the electrode plate is 2N / m to 10N / m.
8. The diaphragm according to claim 1 or 2, characterized in that: The glue dots include polymer particles, and the material of the polymer particles is selected from at least one of polyvinylidene fluoride and polymethyl methacrylate.
9. A method for preparing a diaphragm according to any one of claims 1 to 8, characterized in that: The following steps are involved: Dispensing a glue layer solution onto at least one side of the surface of the base film to form an initial structure of glue dots distributed in a dot matrix, wherein the glue layer solution includes a first solvent; Dispensing a second solvent onto the surface of the initial structure of the glue dots to form a second solvent droplet, wherein the second solvent is a solvent that is insoluble or slightly soluble in the first solvent; The initial structure of the glue dots having the second solvent droplets on the surface is subjected to a heating treatment. While the second solvent droplets are evaporated by the heat, the initial structure of the glue dots is cured by the heat to form the glue dots.
10. The method for preparing a diaphragm according to claim 9, characterized in that: The temperature of the heating treatment is 60°C to 90°C, and the boiling point of the second solvent is not higher than 90°C.
11. The method for preparing a diaphragm according to claim 9, characterized in that: The second solvent droplet has a thickness of 1 μm to 13 μm and a diameter of 200 μm to 1000 μm.
12. The method for preparing a diaphragm according to claim 9, characterized in that: The first solvent is selected from water, and the second solvent is selected from at least one of dichloromethane, dichloroethane and carbon tetrachloride; Alternatively, the first solvent is selected from at least one of dimethylacetamide and N-methylpyrrolidone, and the second solvent is selected from at least one of cyclohexane and cyclopentane.
13. A battery, characterized in that: A diaphragm comprising any one of claims 1 to 8, or a diaphragm obtained by the method for preparing the diaphragm according to any one of claims 9 to 12.
14. An energy storage device, characterized in that: The invention comprises a casing and at least one battery according to claim 13, wherein the battery is accommodated in the casing.
15. An electrical equipment, characterized in that: It includes the energy storage device as described in claim 14, and the energy storage device supplies power to the electrical equipment.
Citation Information
Patent Citations
Diaphragm, secondary battery, and electric device
CN116799438A
Cited By
Diaphragm and preparation method thereof, battery and electric equipment
CN121394782A
Dispensing diaphragm as well as preparation method and application thereof
CN121440043A
Separator, battery, energy storage device, and electric equipment comprising the same
WO2026194622A1